Cytotaxonomic studies on some Vicia L. species growing in eastern Mediterranean and southern Aegean regions, I - Tabur, S; Civelek, S; Bagci, E (Soc Botanique France, 2001)
In this study, some natural Vicia L. species growing in eastern Mediterranean and south Aegean regions have been investigated morphologically and cytotaxonomically. Morphology, chromosome number and morphometries of nine taxa belonging to Vicia L. genus including Vicia cracca L. subsp, tenuifolia (Roth) Gaudin, V cracca L. subsp. stenophylla Vel., V villosa Roth subsp. dasycarpa (Ten.) Cav., V articulata Hornem., V cappadocica Boiss, & Bail, V ervilia (L.) Willd., V tetrasperma (L.) Schreb,, V laxiflora Brot., V hirsuta (L.) S.F. Gray have been studied by using karyologic and numeric taxonomical techniques. Data obtained on morphologic character, chromosome measurements and morphometric analysis were analysed by using cluster analysis. It is found that the whole studied Vicia species have 2n = 14 chromosomes (X = 7), In the result, it is found that the karyotypes of the studied Vicia taxa were congruent with the studied morphological characters. Close genetical relationships were determined.
Keywords: Vicia; cytotaxonomy; chromosome; karyotype; numerical taxonomy